The Emotional Intelligence Of Final Semester Students Of English Department In Facing The Thesis Writing At University Of Sembilanbelas November, Kolaka - Karman Karman; Ummy Chalzum (EDUCATIO : Journal of Education, 2017)
This study was aimed at determining the level of emotional intelligence and find out the dominant aspect of the emotional intelligence of final semester students of English Department at University of Sembilanbelas November, Kolaka. This study was a survey research. The respondents in this study were the final level students of English Department. The number of respondents in this study was 40 respondents. The instruments of this study were a questionnaire and interview guideline. The sampling technique was quota sampling technique. Based on the analysis of the result of the Mean and Standard Deviation, 37 respondents or 92.5% had a standard level of emotional intelligence and 3 respondents or 7.5% had a high level of emotional intelligence. From the result of the calculation of the data, the ideal Mean (Mi) and the ideal Standard Deviation (SDi) of each aspect of emotional intelligence, it was found that the dominant aspect in students’ emotional intelligence was self-awareness, then followed by the aspect of empathy, then followed by the aspect of motivation, and then the aspect of social skills, and the latter was aspect of self-setting. To add, the level of their emotional intelligence was categorized as very high with SD.